Improved Meet-in-the-Middle Attacks on Reduced-Round Tweakable Block Cipher Deoxys-BC. (2nd June 2021) - Li, Manman; Chen, Shaozhen
Abstract: Deoxys-BC is an internal tweakable block cipher of the authenticated encryption algorithm Deoxys, which is a third-round finalist in the CAESAR competition. In this paper, we study the property of Deoxys-BC, such as the subtweakey difference cancelation and the freedom of the tweak. Combining the differential enumeration technique with these properties, the authors achieve the key-recovery attacks on Deoxys-BC under the meet-in-the-middle attack. As a result, we get an attack on 9-round Deoxys-BC-128-128 by constructing a 6-round meet-in-the-middle distinguisher with 2^113 plaintext–tweak combinations, 2^97 Deoxys-BC blocks and 2^121.6 9-round Deoxys-BC-128-128 encryptions. We also present an attack on 11-round Deoxys-BC-256-128 for the first time by constructing a 7-round meet-in-the-middle distinguisher with 2^113 plaintext-tweak combinations, 2^226 Deoxys-BC blocks and 2^251 11-round Deoxys-BC-256-128 encryptions.